Classifications of Cardiomyopathies - Frequent Updating, Modifications and Re-Classifications in the Era Of Molecular Medicine and the Past Decades - Kauser, Mohammad Abu; Safiuddin, Mohammad; Safi, Shahnaz Binte (University Heart Journal, 2013)
Abstract not available DOI: http://dx.doi.org/10.3329/uhj.v8i2.16085 University Heart Journal Vol. 8, No. 2, July 2012